METHOD FOR BUILDING A KEY CYBERSECURITY RISK FACTORS PROFILE OF MODERN DISTRIBUTED INFORMATION SYSTEMS - Palko, Dmytro; Myrutenko, Larysa (Ukrainian Information Security Research Journal, 2024)
The assessment and analysis of cybersecurity risks are fundamental aspects of developing a reliable and effective information security management system, especially in the context of rapid technological advancements and the increasing complexity of modern distributed information systems. Traditional risk assessment methods, which are primarily based on conceptual approaches and classical techniques, have several limitations and prove to be inefficient in large-scale distributed systems. These methods fail to account for the dynamic nature of the environment and do not provide an effective analysis of interdependencies between numerous risk factors. This study proposes a method for constructing a profile of key risk factors in modern distributed information systems based on correlation analysis and modeling of their interrelationships. This approach enhances the efficiency of cybersecurity risk assessment in dynamic environments. Additionally, the proposed method was used to develop a profile of key risk factors for modern distributed systems, analyze their statistical significance and correlation, and identify and structure priority information security measures and controls, which demonstrate high efficiency in distributed environments, considering both technological and organizational aspects, ensure a systematic approach to information security risk management, reduce the impact of threats, and enhance the resilience of distributed systems against potential attacks. The proposed approach to optimizing the selection of input features and identifying the most significant risk factors, based on the developed risk factor profile for modern distributed information systems, demonstrated comparable numerical results with factor analysis using the principal component analysis (PCA) – method 42 selected metrics versus 40 for PCA. However, it provided a 4% improvement in overall classification accuracy for the designed cybersecurity risk assessment models in DIS compared to the PCA-based control model. This confirms its effectiveness in the context of adaptive risk analysis in distributed environments.